2011
DOI: 10.1002/hup.1161
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin as a biomarker for treatment response and tardive dyskinesia in schizophrenia subjects: old thoughts revisited from a genetic perspective

Abstract: Previous studies investigated whether prolactin (PRL) serum level was a biomarker of antipsychotic response, schizophrenia symptomatology, and tardive dyskinesia. Most of the findings support that antipsychotic drugs modulate PRL levels but PRL is not a steady indicator. Recent results suggest a genetic effect of PRL and PRL receptor (PRLR) polymorphisms in PRL levels indicating that independently of antipsychotic therapy subjects could have altered PRL levels due to their genetic background.We evaluated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…They found that the G allele was significantly more common in patients, particularly in males, and pointed out that this variation was similar to that reported in autoimmune diseases. Souza et al [53] examined the association between the prolactin and prolactin receptor (PRLR) genes and both tardive dyskinesia and treatment response but failed to find a significant association in either case.…”
Section: Genetic Studies Of Prolactin In Schizophreniamentioning
confidence: 99%
“…They found that the G allele was significantly more common in patients, particularly in males, and pointed out that this variation was similar to that reported in autoimmune diseases. Souza et al [53] examined the association between the prolactin and prolactin receptor (PRLR) genes and both tardive dyskinesia and treatment response but failed to find a significant association in either case.…”
Section: Genetic Studies Of Prolactin In Schizophreniamentioning
confidence: 99%
“… 50 In a preliminary study done in patients with SZ, genetic variation at the prolactin and prolactin receptor loci were not associated with: 1) prolactin serum levels; 51 2) patients who do not respond to antipsychotic treatment; or 3) patients who have tardive dyskinesia. 52 Serum prolactin levels are primarily under dopaminergic control and increase in response to D2 antagonists such as haloperidol, blockade of monoamine transporters that decrease extracellular dopamine such as reserpine, but do not change significantly in response to partial D2 agonists such as aripiprazole. 53 …”
Section: Discussionmentioning
confidence: 99%
“…The existence of PDE4B gene variants was examined in a population of 169 Caucasian patients taking antipsychotic medication. Two PDE4B variants associated with tardive dyskinesia and two additional variants associated with female-specific tardive dyskinesia were discovered (Souza et al, 2011). However, correction for multiple testing eliminated these variants as being truly genetically associated with the tardive dyskinesia observed in schizophrenia.…”
Section: Associated Phenotype Referencesmentioning
confidence: 99%